Norms from Above, Movements from Below - Ferth Vandensteen Manaysay (Jember University Press, 2020)
This article seeks to analyse how conceptions of global climate change norms have contributed to the framing strategies and tactics of local indigenous people’s rights movements using the cases of Cordillera Peoples’ Alliance (CPA) from the Philippines and the Aliansi Masyarakat Adat Nusantara (AMAN) from Indonesia. Drawing on the combined theoretical frameworks of the world society approach and the social movement framing theory, this article argues that global climate change norms have provided indigenous people’s rights movements in Indonesia and the Philippines with new sources of vocabularies towards collective action. In theoretical and empirical terms, it contends that the exposure of the local indigenous social movements to global normative mechanisms have shifted local activism, as the world society approach envisages, while framing theory elucidates the manner in which movement-actors are able to interpret and transform the ideas they receive. A paired comparison, based on data collected from the CPA and AMAN’s public pronouncements as well as in-depth interviews with local indigenous movement leaders and members, shows material ideas and instruments that social movements receive from global institutional sources (such as the United Nations climate change agreements, global indigenous declarations, and international climate justice coalitions) have enabled them to produce novel frames for collective action at the local level. Contrastingly, it demonstrates how indigenous climate justice activists have also been able to frame their contentions against the prevailing global norms and ideas about climate change.